Influence of the Brace Configurations on the Seismic Performance of Steel Concentrically Braced Frames - Yang, T. Y.; Sheikh, Hediyeh; Tobber, Lisa (Frontiers in Built Environment, 2019)
Concentrically braced frame is an effective and prevalent seismic force resisting system which is commonly used in low-rise buildings. This type of structural system utilizes steel braces to provide the stiffness and strength needed to dissipate earthquake energy. Several bracing configurations have been proposed in different building codes worldwide. These codes provide detailed design requirements for the structural members and connections, but no guidance is provided in selecting the best bracing configuration for the design. In this study, the impact of the bracing configuration on the seismic response of a five-story prototype office building located in Vancouver, Canada, is systematically examined. Five different bracing configurations were designed according to the National Building Code of Canada and CSA S16 standard. Detailed structural responses, initial costs, and life cycle costs of the prototype building with five different bracing configurations were systematically compared. The results show that the different bracing configurations play an important role in sizing the structural members, which impacts the initial material usage and the overall life cycle cost of the building.